Effects of Atorvastatin on E-Selectin and Myeloperoxidase Expressions After Cerebral Ischemia-Reperfusion Injury in Rats - Zhong, W.; Wu, W.; Cao, H.; Tu, Q.; Tang, X. (Нейрофизиология, 2014)
We examined expressions of E-selectin and myeloperoxidase (MPO) in cerebral tissues after cerebral ischemia-reperfusion (CIR) in rats and evaluated neuroprotective effects of atorvastatin under these conditions. Immunohistochemical methods were used to detect E-selectin and MPO expressioning tissue. Small numbers of E-selectin- and MPO-positive cells were observed in the sham group within 4 to 24 h time intervals. In the operation group, numerous positive cells were found in the cortex and hippocampus after CIR. E-selectin expression occurred at 4 h, peaked at 12 h, and returned to nearly normal levels at 24 h. However, E-selectin expression in the intervention (CIR + atorvastatin) group was significantly lower than that in the operation group at each time (P < 0.05). Myeloperoxidase had nearly similar timing of changes in E-selectin expression, and MPO expressions at different time points in the intervention group were significantly lower than those in the operation group (P < 0.05). Therefore, expressions of E-selectin and MPO change dynamically after CIR. Atorvastatin, an agent having anti-inflammatory properties, demonstrates an obvious protective effect with respect to acute CIR-related damage.